The Willingness to Pay—Willingness to Accept Gap, the "Endowment Effect," Subject Misconceptions, and Experimental Procedures for Eliciting Valuations: Comment - Isoni, Andrea; Loomes, Graham; Sugden, Robert (The American economic review, 2011)
Plott and Zeiler (2005) report that the willingness-to-pay/willingness-to-accept disparity is absent for mugs in a particular experimental setting, designed to neutralize misconceptions about the procedures used to elicit valuations. This result has received sustained attention in the literature. However, other data from that same study, not published in that paper, exhibit a significant and persistent disparity when the same experimental procedures are applied to lotteries. We report new data confirming both results, thereby suggesting that the presence or absence of a disparity may be a more complex issue than some may have supposed. (JEL C91, D12, D81, D83)